2021
DOI: 10.1088/1755-1315/746/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Key drivers of organic rice productivity in Sleman and Magelang Regencies

Abstract: Organic farming system in Indonesia had been growing continuously in the recent years. Organic label could only be put on products which were complied with organic standards and regulations as well as certification requirements. As the world became more global, in addition to organic national certification, Indonesian organic farmers needed to comply with international organic certification so that they could enter the open market. This study attempted to: (1) provide a descriptive analysis of rice organic far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Organic vegetable farmers apply more adaptation strategies than conventional farmers [ 48 ]. Farmers more aware of climate change will implement more adaptation strategies to mitigate the effects of climate change [ 54 – 56 ]. The adaptation strategies most commonly implemented by organic farmers compared to conventional farmers are mixed cropping, crop rotation, shade, increasing the dose of organic manure, and changing irrigation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Organic vegetable farmers apply more adaptation strategies than conventional farmers [ 48 ]. Farmers more aware of climate change will implement more adaptation strategies to mitigate the effects of climate change [ 54 – 56 ]. The adaptation strategies most commonly implemented by organic farmers compared to conventional farmers are mixed cropping, crop rotation, shade, increasing the dose of organic manure, and changing irrigation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of various local raw materials, more efficient use of labor and machinery, open access to business capital and improvement of technological innovation-information access, and better price incentives for organic products will be important factors to increase organic rice productivity. The study of organic rice in Central Java and Yogyakarta by Devi et al (2021) showed the highest productivity in the Pakem area of Yogyakarta Province reaching 7.5 tones/ ha and in the Sawangan area of Central Java Province reaching 8 tons/ha. This shows that if organic rice farming can be managed properly following standard procedures and supported by various appropriate conditions, it will be able to achieve high productivity exceeding the average rice production in Vietnam.…”
Section: Results and Discussion A Governance Of Organic Agriculture D...mentioning
confidence: 98%
“…Therefore, the determination of organic farming areas needs to be realized to improve farming efficiency and ensure the sustainability of the organic farming system. The development of zoning-based organic farming is based on several justifications, including (Devi et al, 2021;Irham et al, 2020;Wirakusuma et al, 2019): (1) As a sustainable agricultural system (ecological, social, and economic multiplier effects), (2) Having a higher selling price (premium), (3) Efficient use of inputs, (4) high export opportunities to other countries, (5) opportunities to improve farmer welfare, and (6) development of a farm record system as part of a modern farming system will be easier to implement the organic zone as management innovation system becomes attractive as a strategic solution in producing healthy food, as well as improving the quality of land and the environment as well as improving the welfare of farmers through increasing food production, increasing business efficiency, and improving food prices. Organic farming is technically more efficient if it is carried out by recommended organic practices and is carried out within an area.…”
Section: Introductionmentioning
confidence: 99%
“…The expansive and productive terrain enables expanded organic paddy production. This endeavor is difficult because farmers encounter obstacles, such as a small percentage of certified organic agricultural land and the high risk of organic paddy production [21][22]. According to the Ministry of Agriculture [23], certifying agricultural land, particularly paddy production, boosts the product's added value and competitiveness [24].…”
Section: Introductionmentioning
confidence: 99%